PODCAST: POTENSI DAN PERTUMBUHANNYA DI INDONESIA - Irwansyah; Rafiza Nur Rafiza (UNIVERSITAS STEKOM, 2020)
Abstract: In the digital age which allows anyone by their smartphone to record videos and upload them online, it is surprising that audio not only survives, but also develops. Podcasts — audio file that can be downloaded to digital devices to be played later—starts being familiar. Podcasts are growing, unfortunately they are still not widely used both academically dan practically in Indonesia as they should in America and Europe. Since the lack of conceptual papers about podcast, this article aims to develop an understanding of podcasts. The research method applied is library research based on various references relating to keywords and research areas. The results show that podcasts in Indonesia are starting to grow and attract the attention of people in Indonesia, especially on Java. Podcasts as audio media have the potential to be used in the fields of education, tourism industry, and opportunities for growth in Indonesia.